2011
DOI: 10.18632/aging.100279
|View full text |Cite
|
Sign up to set email alerts
|

RasGrf1 deficiency delays aging in mice

Abstract: RasGRF1 is a Ras-guanine nucleotide exchange factor implicated in a variety of physiological processes including learning and memory and glucose homeostasis. To determine the role of RASGRF1 in aging, lifespan and metabolic parameters were analyzed in aged RasGrf1−/− mice. We observed that mice deficient for RasGrf1−/− display an increase in average and most importantly, in maximal lifespan (20% higher than controls). This was not due to the role of Ras in cancer because tumor-free survival was also enhanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 59 publications
4
64
0
Order By: Relevance
“…Our findings seem to conflict with an intact insulin response of ex vivo islets from adult Rasgrf1 null mice (12) which display a reduced body size, blood metabolomic profiles resembling calorie-restricted mice, increased life span, and Sirt1 expression (10). Sirt1 can promote glucose-dependent insulin secretion (9) and might have masked any deficits from impaired Rasgrf1 signaling in adult mice.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings seem to conflict with an intact insulin response of ex vivo islets from adult Rasgrf1 null mice (12) which display a reduced body size, blood metabolomic profiles resembling calorie-restricted mice, increased life span, and Sirt1 expression (10). Sirt1 can promote glucose-dependent insulin secretion (9) and might have masked any deficits from impaired Rasgrf1 signaling in adult mice.…”
Section: Discussionmentioning
confidence: 76%
“…-/-mice (Borras et al 2011;de Magalhaes 2011;Kawahara and Kono 2010). It is also well known that changes in IIS have important implications for aging, and comparable effects on the extension of longevity can be produced by CR that attenuates IIS (Fontana et al 2010;Masoro 2005).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, mice with high levels of circulating IGF-I (e.g., transgenic mice that overexpress bovine growth hormone [bGH]) have significantly reduced life span (Bartke and Brown-Borg 2004;Bartke et al 2002;Bonkowski et al 2006;Coschigano et al 2000;Zhou et al 1997). Furthermore, as recently demonstrated, mice with attenuated expression of RasGRF1, a small GTP exchange factor (GEF) for Ras, also live longer (Borras et al 2011). This latter finding can be explained by the involvement of RasGRF1 in signaling through insulin and insulinlike growth factor-1 receptors (InsR and IGF-IR, respectively), as we have recently proposed (Ratajczak et al 2011d).…”
Section: Introductionmentioning
confidence: 99%
“…The animal studies showed that RASGEF1A, an evolutionary conserved gene, is paternally imprinted in mice and regulates longevity as well as embryogenesis [77]. Besides delays in aging, RASGEF1A deficient mice possessed enhanced tumor free survival, and protection against oxidative stress [78]. In humans is RASGEF1A probably not imprinted and serves as an in vivo activator for H-RAS and members of the R-RAS and RAC subfamilies [79], regulator of glucose metabolism and insulininsulin like growth factor signaling [80] and/or is involved in cell-cell adhesion [76,81].…”
Section: Bcl6 Gene Rearrangements In Dlbclmentioning
confidence: 99%